Motivación y Rendimiento académico de los estudiantes de secundaria en un centro Etnoeducativo de la ciudad de Riohacha. (2023)
As one of the most important factors from which the educational quality of an institution is defined, the academic performance of students is a process that must be evaluated from a series of elements that will contribute to its level, whether it is presented in a positive or negative way, according to certain measurement scales, and therefore, in any of the cases, attention must be paid to the specific causes that affect such results.